Construction of Zn(ii) and Cd(ii) metal–organic frameworks of diimidazole and dicarboxylate mixed ligands for the catalytic photodegradation of rhodamine B in water. Issue 9 (10th December 2014) - Lü, Chun-Ning; Chen, Min-Min; Zhang, Wen-Hua; Li, Duan-Xiu; Dai, Ming; Lang, Jian-Ping
Abstract : Four metal–organic frameworks were prepared, all of which exhibited good catalytic performance for the photodegradation of rhodamine B in water. Abstract : A set of four metal–organic frameworks, namely, [Zn(1, 3-BDC)(bmimb)] n (1 ), [Zn(1, 4-BDC)(bmimb)] n (2 ), [Cd(1, 3-BDC)(bmimb)] n (3 ), and [Cd(1, 4-BDC)(bmimb)] n (4 ), have been prepared under solvothermal conditions (1, 3-BDC = 1, 3-benzenedicarboxylate; 1, 4-BDC = 1, 4-benzenedicarboxylate; bmimb = 4, 4′-bis(4-methyl-1-imidazolyl)biphenyl). The long bmimb ligand (N⋯N separation of ca. 14.1 Å) induces interpenetration of1, 2 and4 to increase both the framework stability and the density of effective catalytic metal centers. Compounds1, 2 and4 are interpenetrated 3D structures while3 features a 2D structure. Compound1 exhibits a parallel 2D → 3D polycatenation while2 and4 are isomorphous and feature 3D → 3D interpenetration. Compounds1–4 fluoresce in the range of 350–372 nm in the solid state, whereas compounds2 and3 catalyze the almost complete photodegradation of rhodamine B (RhB) in water within ca. 4 h and can be recycled at least five times without loss in their crystallinity.